'Have we any mother Juliana's among us?': The multiple identities of Julian of Norwich in Restoration England. Issue 3 (30th March 2017) - Temple, Liam
Abstract : The true identity of the fourteenth-century anchoress Julian of Norwich has been lost to history. Yet in the seventeenth century Catholic and Protestant polemicists created different 'Julians' to construct and contrast their own confessional positions. This article traces the different identities prescribed to Julian and argues that they allow us fresh insight into some of the most prevalent religious and political issues of Restoration England. It begins by tracing the positive reception of Julian's theology among the Benedictine nuns of Paris and Cambrai, including the role of Augustine Baker in editing Julian's text. It then explores how the Benedictine Serenus Cressy and the Anglican Edward Stillingfleet created different identities for Julian in their ongoing polemical battles in the Restoration period. For Cressy, Julian was proof of the strength of Catholic devotional and spiritual traditions, while Stillingfleet believed she was evidence of the religious melancholy encouraged by monasticism. By exploring these identities, this article offers new perspective on issues of Catholic loyalty, enthusiasm, sectarianism and doctrinal authority.